The Action of Paraquat on the Incorporation of Palmitic Acid into Dipalmitoyl Lecithin in Mouse Lungs - Fletcher, K. (1972)
Control mice injected with tritium labelled palmitic acid incorporated radioactivity into dipalmitoyl lecithin in their lungs within 30 seconds. The labelling disappeared with a mean half-life of approximately 15 hours. Treatment with paraquat apparently affected neither the amount of dipalmitoyl lecithin present nor its rate of destruction.